Can We Predict the Surgical Margin Positivity in Patients Treated with Radical Prostatectomy? A Multicenter Cohort of Turkish Association of Uro-Oncology - Bolat, Deniz; Eskicorapci, Saadettin; Karabulut, Erdem; Baltaci, Sumer; Yildirim, Asif; Sozen, Sinan; Ates, Ferhat; Sekerci, Cagri Akin; Kurtulus, Fatih; Dirim, Ayhan; Muezzioglu, Talha; Can, Cavit; et al. (GALENOS YAYINCILIK, 2015)
Objective To analyze the parameters that predict the surgical margin positivity after radical prostatectomy for localized prostate cancer. Materials and Methods In this multicenter study, the data of 1607 consecutive patients undergoing radical prostatectomy for localized prostate cancer in 12 different clinics in Turkey between 1993-2011 were assessed. Patients who had neoadjuvant treatment were excluded. We assessed the relationship between potential predictive factors and surgical margin status after radical prostatectomy such as age, cancer characteristics, history of transurethral prostate resection, surgical experience and nerve-sparing technique by using univariate and multivariate Cox regression analyses and t test. Results The overall surgical margin positivity rate was 22.6\% (359 patients). In univariate analyses, preoperative prostate specific antigen level, clinical stage, biopsy Gleason score, percentage of tumor involvement per biopsy specimen, transurethral prostate resection history, surgical experience and nerve-sparing technique were significantly associated with positive surgical margin rate. In multivariate analyses, preoperative prostate specific antigen level (OR: 1.03, p=0.06), percentage of tumor involvement per biopsy specimen (OR: 7,14, p<0,001), surgical experience (OR: 2.35, p=0.011) and unilateral nerve-sparing technique (OR: 1.81, p=0.018) were independent predictive factors for surgical margin positivity. Conclusion Preoperative prostate specific antigen level, percentage of tumor involvement per biopsy specimen, surgical experience and nerve-sparing technique are the most important predictive factors of surgical margin positivity in patients undergoing radical prostatectomy for localized prostate cancer.
Keywords: Prostate cancer; radical prostatectomy; surgical margin; PSA; percentage of tumor involvement; surgical experience; nerve sparing technique